A política de educação integral em tempo integral, na rede pública municipal de ensino de Campinas - SP - Estevão, Daniel Carlos (2022)
The object of study of the present work is the Public Policy of Integral Education of the Municipal Education Network of Campinas - SP. Based on this object, a concern emerged that motivated and directed the development of the research, namely: How was the cycle of the public policy of Inte- gral Education developed in the Municipal Education Network of Campinas (RMEC) - SP? In view of what we have observed, in relation to the development of the cycle of the aforementioned policy, two hypotheses emerged: 1) this policy presented important weaknesses since its genesis and, to date, it is not consolidated and, 2) the forces involved that act in relation to this policy, with regard to the objectives, they are divergent. Presenting the policy and investigating how it was constituted was the general objective of this work. We also had as a specific objective: to dialectically analyze the development of the policy, from its implementation, in 2014, to its evaluation by the actors in- volved in the process, in the context of the commissions and working groups established for this purpose, in the years 2019 to 2021 The theoretical references chosen for the analysis of the research object were the Critical Theory of the Frankfurt School and other critical theorists. This case study was developed through the methodological approach of the Policy Cycle Approach, or the Policy Cycle Approach, and also through data collection, based on the reading and analysis of official doc- uments from the Campinas Municipal Education Department (SME) on the Educational proposal of integral education schools in the municipality, as well as field research, in which we participated, specifically during the work of the Study Commissions and Working Groups, composed of students and their guardians; teachers and managers of educational units and the SME, trained to evaluate the aforementioned policy. We defend the thesis and conclude that the public policy of integral edu- cation of the RMEC, so far, has not been consolidated and is subject to discontinuity, common to policies in this field. Nevertheless, the movement of policy evaluation, analyzed in this work, and the collective effort to do so, point to the existence of an immeasurable will of the different actors so that the educational policy in question, finally, is consolidated. The first steps have been taken. We hope, as we also hope, that the movement started will last and that integral education in the RMEC will become a permanent reality, for the benefit of future generations.